2020
DOI: 10.3390/ma13225218
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Utilization of Coal Fly Ash Derived Grog in Clay Ceramics

Abstract: Grog is an additive material that plays important roles in ceramic making. It improves the fabrication process of green bodies as well as the physical properties of fired bodies. Few low-cost materials and wastes have found their application as grog in recent years, thus encouraging the replacement of commercial grogs with cost-saving materials. Coal fly ash, a combustion waste produced by coal-fired power plant, has the potential to be converted into grog owing to its small particle sizes and high content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Monolithic B 4 C ceramic is an extremely stiff, robust, and hard low-density material. In order to create a strong low-density material, LM6-B 4 C-Fly ash composites can conglomerate the very high stiffness and excellent hardness of B 4 C with the Aluminium ductility (Choo et al, 2020;Ghandvar et al, 2021). From the density results, it can be interpreted that a reduction in density is required to fabricate lightweight composite materials.…”
Section: Mass Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Monolithic B 4 C ceramic is an extremely stiff, robust, and hard low-density material. In order to create a strong low-density material, LM6-B 4 C-Fly ash composites can conglomerate the very high stiffness and excellent hardness of B 4 C with the Aluminium ductility (Choo et al, 2020;Ghandvar et al, 2021). From the density results, it can be interpreted that a reduction in density is required to fabricate lightweight composite materials.…”
Section: Mass Volumementioning
confidence: 99%
“…It has been found that increasing sliding velocity decreases the WR and friction coefficient. It is hypothesized that the transfer layer on MMC serves as a protective layer, slowing down wear and reducing friction (Choo et al, 2020). The SWR lowers as the S increases (Uyyuru et al, 2007;Patnaik et al, 2022).…”
Section: Effect Of Load On Swrmentioning
confidence: 99%
“…The most valuable information for identifying the potential application of CFA and environmental concerns associated with CFAs is provided by the classification system based on their origin, phase-mineral and chemical composition, properties, and behavior [8]. CFAs containing a large amount of CaO, SiO 2 , Al 2 O 3 , and glass phase, having fine-grained powder morphology, can be a good raw material for manufacturing cost-effective sintered products, such as glass and ceramics [9][10][11][12], light-weight aggregates [4,13,14], and filtration membranes [15,16], as well as building ceramic [17] and ceramic mixtures [18], cementitious composites [19], geopolymer [20][21][22], etc. From both an economic and an environmental viewpoint, the production of sintered materials only from CFA without the addition of natural raw materials, nucleating agents, various waste and organic binders is of particular interest [10,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…At present, many researchers are focusing on this topic, and construction and building materials have been considered as the best way to reuse such an enormous amount of industry silicate solid wastes [ 1 ]. For instance, steel slag has been successfully used in pavement engineering [ 2 , 3 , 4 ], fly ash is widely reused as cementitious materials in concrete [ 5 , 6 , 7 ], and waste tire rubber can be reused to improve the rutting resistance of asphalt pavement [ 8 , 9 , 10 ]. Along with these developments, there are still many challenges that should be further discussed.…”
mentioning
confidence: 99%
“…The corrosion resistance of the cement-ground granulated blast furnace slag system and cement-fly ash system was compared by adding NaCl in the paste. While in the research from Choo, the coal fly ash, which is a combustion waste produced by a coal-fired power plant, was recycled in the production of clay ceramics [ 5 ]. An environment-friendly preparation method of reaction-bonded silicon carbide ceramics was reported by Ye [ 12 ].…”
mentioning
confidence: 99%